1996
DOI: 10.1016/s0735-1097(96)00324-5
|View full text |Cite
|
Sign up to set email alerts
|

Thrombogenicity of radiofrequency lesions: Results with serial D-dimer determinations

Abstract: As reflected by elevated plasma D-dimer levels, RF ablation has a thrombogenic effect that persists through 48 h after the procedure. This effect needs to be taken into account when considering antithrombotic therapy in patients undergoing RF ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 15 publications
1
26
0
3
Order By: Relevance
“…7 Another report showed that platelet aggregability increased during RF current delivery, 9 and Manolis et al showed that RF-CA provoked an elevation in the D-dimer concentration by 48 h after the procedure. 8 These previous studies have not fully elucidated the influence of the RF current on thrombus formation nor have they observed the delayed phase of thrombogenesis. Previous experimental studies have shown histological changes in association with RF-CA, 10,18,19 one of which is thrombus formation 7 days after the procedure.…”
Section: Thrombogenesis Caused By Radiofrequency Currentmentioning
confidence: 99%
“…7 Another report showed that platelet aggregability increased during RF current delivery, 9 and Manolis et al showed that RF-CA provoked an elevation in the D-dimer concentration by 48 h after the procedure. 8 These previous studies have not fully elucidated the influence of the RF current on thrombus formation nor have they observed the delayed phase of thrombogenesis. Previous experimental studies have shown histological changes in association with RF-CA, 10,18,19 one of which is thrombus formation 7 days after the procedure.…”
Section: Thrombogenesis Caused By Radiofrequency Currentmentioning
confidence: 99%
“…Manolis et al 540 and Michelucci et al 541 separately studied activation of the clotting system, comparing patients who had routine electrophysiology studies with patients who had RFCA procedures. Spontaneous platelet aggregation, prothrombin fragment 1+2, thrombin-antithrombin complex, and d-dimer levels increased in all patients.…”
Section: Radiofrequency Catheter Ablationmentioning
confidence: 99%
“…The TAT level then returned to baseline level 48 h after both left-heart and right-heart procedures, suggesting that the RF ablation procedure itself induced the active thrombogenic process, which is consistent with previous findings in the literature. 4,7 D-dimer assay is recognized as highly sensitive (> 90%) with a high negative predictive value, making it a very useful clinical tool for detecting vascular thrombosis. 4 Although the elevation of D-dimer may result from the peripheral effects induced by sheath insertion and catheter manipulation, 10 the marked elevation of D-dimer in this study mainly resulted from the central effects of RF ablation application, which caused endomyocardial injury and higher temperature.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 D-dimer assay is recognized as highly sensitive (> 90%) with a high negative predictive value, making it a very useful clinical tool for detecting vascular thrombosis. 4 Although the elevation of D-dimer may result from the peripheral effects induced by sheath insertion and catheter manipulation, 10 the marked elevation of D-dimer in this study mainly resulted from the central effects of RF ablation application, which caused endomyocardial injury and higher temperature. 7,16 In contrast to TAT, which returned to its baseline level at 48 h post procedure, the plasma level of D-dimer remained elevated in both groups and was slightly higher in the AVNRT group at 48 h post procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation